Kshana-The Smallest Mysterious Unit of Time Exploring the Temporal Variation of Fine Structure Constant - Shesharao M. Wanjerkhede (Fundamental Research and Application of Physical Science Vol. 8, 2023)
Max Planck (1899) proposed universally meaningful natural unit of time that would be less arbitrary, less human-oriented than second. Whereas Maharishi Vyasa defined a much more human-oriented and meaningful time unit ‘kshana’ or ‘moment’ which is constant, exceedingly small and which cannot be further divided and is independent of external perturbations as compared with the time unit second in SI system of units. The validation of ‘kshana’ produces accurate results for physical quantities such as fine structure constant and Rydberg constant. During the validation, it was also found that the fine structure constant is inversely proportional to the speed of light and the time variation of Bohr magneton is half the time variation of the fine structure constant. Calculations have also shown that the time taken by an electron to complete one revolution in the first orbit of hydrogen atom is 4 ‘kshanas’ and for higher orbits the time periods are 32, 108, 256, 500..., ‘kshanas’ which are in whole numbers whereas the time periods calculated in seconds are in fractions. The unit of time ‘kshana’ is consistent with modern time units and can solve the problems at subatomic level and can also be useful for classifying the two or more elementary particles having the same origin, characteristics, and place at a particular time of ‘moment’ or ‘kshana’. Since two ‘moments’ or ‘kshanas’ at a time do not coexist and by succession also they are different, because it is not possible.